Preparation and Application of Tetracycline Hydrochloride Liquid membrane Electrodes. - Abass, Amina M (Al-Nahrain Journal of Science, 2018)
Two liquid membrane electrodes for (TCH) were prepared by using ion pair which included phosphomolybdic acid (PMA)-(TCH) with plasticizers: Di-n-butyl phthalate(DBPH), and di-octylphenylphosphonate (DOPH). Tetracycline electrodes were gave a Nernstain response equal to 56. 51 and 50. 66 mV/decade for membranes depended on DBPH and DOPH as a plastisizers, respectively. Linear ranges were around 6. 8×10-6- 1. 0×10-1 and 1. 0×10-5-1. 0×10-1 M, respectively. Detection limit were equal to 4. 0×10-6, 5. 0×10-6 M, respectively. PH range were also studied at three different concentration of tetracycline solutions. As well as were studied lifetime, selectivity, potentiometric methods such as direct, standard addition , multiple standard addition and titration methods were applied to determination tetracycline in pharmaceutical preparation